Scalar sector interactions in BDW model - Hieu, Tran Minh; Sang, Dinh Quang (VNU Journal of Science: Mathematics - Physics; Vol 40 No 1DO - 10.25073/2588-1124/vnumap.4907, 2024)
In the Bélanger-Delaunay-Westhoff model, vectorlike fermions and a new scalar sector charged under an extra Abelian gauge symmetry are introduced to explain the flavor observables, and the muon . In this paper, we focus our study to the scalar sector of this model and the relevant interactions. The interaction terms including the exotic Yukawa, the gauge interactions, and the scalar 3-point and 4-point interactions are derived together with the corresponding Feynman rules. It is shown that the new scalar  can decay into a pair of standard-model-like Higgs bosons. This channel is considered by analyzing the decay width and its parameter dependence.